Drop-in fuel production with plastic waste pyrolysis oil over catalytic separation. (1st December 2021) - Wang, Shuang; Kim, Hana; Lee, Doyeon; Lee, Yu-Ri; Won, Yooseob; Hwang, Byung Wook; Nam, Hyungseok; Ryu, Ho-Jung; Lee, Kyong-Hwan
Highlights: Pyrolysis oil separator was available for upgrading and separating more diesel grade fuels. Ni-based catalyst showed the highest deoxygenation due to its high strong acid sites. MDC-7 led to more light oil production whereas Ni-based favored more middle oil. Catalytic reactions and coke formation occurred on the strong acid sites. Abstract: The catalytic upgrading of plastic pyrolysis oil was conducted in a 2-kg-scale pyrolysis oil separation system with or without zeolite 4A, Cu-based (MDC-7) and Ni-based catalysts to produce light (F1), middle (F2) and heavy (F3) oil fractions. From the preliminary separation tests without a catalyst, the separation vapor temperature for diesel-like middle fraction (C11 - C22 ) was determined to be in the range of 107–305 °C. After the pyrolysis oil separation with catalysts, the heavy carbon range (>C23 ) sharply decreased from 22.1 wt% in the crude plastic pyrolysis oil to 0.1–1.6 wt% and 7.3–8.4 wt% in the F1 and F2, respectively. Among three catalysts, Ni-based catalyst exhibited the highest deoxygenation capacity (1.23% O in F1 and 0.3% O in F2) owing to its strong acid sites concentration (1.115 mmol/g). Accordingly, the order of the deoxygenation capacity was Ni-based > MDC-7 > zeolite 4A > no catalyst. Moreover, the catalytic reactions (deoxygenation) and coke formation mainly occurred on the strong acid sites. MDC-7 catalyst contributed to more production of C6 –C10 range (15.8 %) with aromatic and naphthenic compounds. In contrast, the major catalytic mechanisms of Ni-based catalyst were dehydration, decarboxylation and decarbonylation reactions. In addition, the physical properties of catalytically upgraded pyrolysis oil were close to those of the petroleum-based fuels. Finally, the current study suggested that Ni-based catalyst was a suitable catalyst for the production of diesel-like fraction (C11 -C12 ) with the lowest contents of oxygen from the plastic pyrolysis oil.